Regional differentiation for life quality of the population in Ukraine under innovative growth - Natalia Burkina; Taras Furman; Janusz Soboń; Konstiantyn Sapun (Financial Internet Quarterly, 2020)
The article focuses on the analysis of economic growth of Ukraine and its regions, using the proposed by the authors indicators of quality and indicators of the population living standards under innovation growth. The main purpose of the research is developing a method of multi-factor assessment and regional classification of population's life quality. Moving to the results literature review showed that many approaches to assessing the quality of life of the population have been developed in the statistical theory and practice. However, still, there are many discussions about the question of a single aggregate indicator of living standards and the methodology of regional differentiation by this criterion. So, it has not been found a rational way to combine indicators of the level and quality of life to obtain a comprehensive index that reflects objectively, reliably and verifiable the population's level and quality of life. The main discovered disadvantage of existing methods is the use of the expert estimation method, which does not allow guaranteeing validity the weight of the criteria for estimation the quality of life indicator. Nevertheless, all authors admitted that today the role of the state rises in solving the most important social and economic problems, therefore, the task to increase the efficiency of the regions' functioning based on innovation activity becomes of key importance.
Keywords: A1; C1; C5; C6; C8; 330; innovative growth; innovation development; living standards of the population; quality of population' s life; regional differentiation; regional clusterization